Upaya Pencegahan Stunting melalui Makanan Bergizi - Nasha Febri; Nissa Ermaulis; Agnes Sherina Simanullang; Indah Cahyani; Ragil Hasudungan; Hendri Saputra; Rivaldo Alfairus (LP2M Universitas Muhammadiyah Enrekang, 2023)
Stunting is a condition characterized by a lack of height when compared to children of their age. Simply put, stunting is a term for growth disorders in children. The main cause of stunting is a lack of nutritional intake during the child's growth. In this journal, I will discuss Stunting Prevention Efforts through Nutritious Food. Pasir Makmur Village, Rambah Samo Subdistrict, Rokan Hulu Regency, Riau is one example of a village that actively performs stunting prevention in its people. The research method used is a qualitative method. Using the Internet media in the form of journals and articles as analysis materials, and direct interviews to the village community, they incorporated ideas found to be their own language style for article materials. This analysis results in anything that can be done to prevent stunting.